The Effect of Body Language Gymnastics on the Decrease in Visceral Fat Members of Pingky Pegandon Gymnastics - Darmawan, Agus; Indriyani, Silvia; Setiawan, Ipang (Journal of Physical Education Health and Sport, 2023)
The accumulation of a lot of fat in the body, because more calories are taken in than expended, is a condition where the body is obese or overweight, and this condition can lead to an increased risk of many diseases. The problem in this study is the lack of physical activity in female members of the Pegandon pinky gymnastics, which results in obesity or a large amount of fat throughout the body. The purpose of this study was to determine the effect of body language exercise on reducing visceral fat in Pingky gymnastics members. This type of research is quantitative with an experimental method using a one-group pretest-posttest research design. The instrument in this study uses BIA (Bioelectrical Impedance Analysis). The research population was members of the Pingky Pegandon Kendal Gymnastics, with a total sample of 22 people. Data analysis used the Prerequisite analysis test in the form of the Shapiro Wilk Normality Test and continued with a different test using the Wilcoxson test calculated using SPSS. The conclusion is that there is an effect of gymnastic body language on reducing visceral fat in Pingky Pegandon Kendal Gymnastics members. Suggestions for maximum results must be consistent and practice at least twice weekly. In addition, you must pay attention to the intake of food eaten by making a checklist of foods eaten for control and also adequate rest so that the body remains in good condition and avoids excess fat in the body.